Exploring the structure and stability of amino acids and glycine peptides in biocompatible ionic liquids. Issue 23 (15th February 2016) - Kumar, Awanish; Bisht, Meena; Venkatesu, Pannuru
Abstract : Amino acids (AAs) are vital components for a variety of biological systems and can be linked through covalent bonds (or peptide bonds) to form a protein structure. Abstract : Amino acids (AAs) are vital components for a variety of biological systems and can be linked through covalent bonds (or peptide bonds) to form a protein structure. Essentially, the interactions of these AAs with solvents as well as co-solvents/solutes determine the thermodynamic stability of the protein. In this context, this review represents an overview of the current status of the thermodynamic effect of ionic liquids (ILs) on AAs and glycine peptides (GPs). Moreover, ILs are considered as green solvents for many chemical and biological processes due to their tunable physical properties. Interestingly, these ILs can adjust themselves in any required experimental conditions such as protein extraction to enzyme catalysis. In this review, we attempt to assess the status of our current understanding on the biocompatible nature of the ions of ILs on AAs and protein model compounds and their functional groups with some precisely available experimental data in the literature. Examples of current applications of the ILs on protein model compounds are also covered in this review.